2023
DOI: 10.3390/children10050832
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Three-Dimensional Imaging, Printing, and Modeling in Pediatric Surgical Oncology: A New Era of Precision Surgery

Arnau Valls-Esteve,
Núria Adell-Gómez,
Albert Pasten
et al.

Abstract: Pediatric surgical oncology is a technically challenging field that relies on CT and MRI as the primary imaging tools for surgical planning. However, recent advances in 3D reconstructions, including Cinematic Rendering, Volume Rendering, 3D modeling, Virtual Reality, Augmented Reality, and 3D printing, are increasingly being used to plan complex cases bringing new insights into pediatric tumors to guide therapeutic decisions and prognosis in different pediatric surgical oncology areas and locations including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, the implementation of enhanced recovery programs in pediatric oncology surgery, as reported by Wells et al 16 , has been shown to improve patient outcomes, underscoring the importance of postoperative management training and specialization. Advancements in surgical approaches, such as the use of three-dimensional (3D) models and augmented reality over conventional imaging for preoperative assessment in Wilms tumor cases 17 , 18 , also emphasize the impact of specialized training. Furthermore, fellowship in pediatric oncologic surgery has been linked to improved survival rates, indicating the positive effect of specialized training on optimizing therapy based on risk stratification algorithms 9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the implementation of enhanced recovery programs in pediatric oncology surgery, as reported by Wells et al 16 , has been shown to improve patient outcomes, underscoring the importance of postoperative management training and specialization. Advancements in surgical approaches, such as the use of three-dimensional (3D) models and augmented reality over conventional imaging for preoperative assessment in Wilms tumor cases 17 , 18 , also emphasize the impact of specialized training. Furthermore, fellowship in pediatric oncologic surgery has been linked to improved survival rates, indicating the positive effect of specialized training on optimizing therapy based on risk stratification algorithms 9 .…”
Section: Resultsmentioning
confidence: 99%
“…These technologies offer an unparalleled depth of insight into complex anatomical structures, enabling surgeons to plan and execute surgical interventions with enhanced precision. 3D reconstructions, including cinematic rendering and volume rendering, provide a detailed visualization of pediatric tumors, significantly aiding in therapeutic decisions and prognostic assessments in various areas such as thoracic, brain, urology, and abdominal surgery 18 . The use of these technologies in the preoperative assessment of children, for instance, in cases like Wilms tumors, has demonstrated potential for guiding surgical decision-making 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It then rendered the tumor and brachial plexus in different colors to improve the sharpness of the tissue edge without redundant background interference. In addition, some studies have also shown that the main innovative imaging reconstruction techniques, 3D modeling technologies (CAD, VR, AR), and 3D printing applications can be helpful in the future preoperative planning of surgery for pediatric tumors ( 30 , 31 ).Therefore, cVRT can accurately show the positional relationship between the tumor and the brachial plexus, which is very important for evaluating its risk, preventing complications, and formulating treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…Post‐processing techniques, including 3D imaging projections (e.g., volume rendering, cinematic rendering, 3D modeling techniques, 3D printing, virtual reality, and augmented reality) enhance surgical planning 48–50 . These technologies enable personalization and 3D visualization of the tumor, surrounding vasculature, and other anatomic structures in the surgical field.…”
Section: Technical Advancesmentioning
confidence: 99%